Leishmaniose visceral : avaliação citomorfológica da medula óssea e correlação com a gravidade da doença - Castro, Alana Jocelina Montenegro de (2011)
The visceral leishmaniasis (VL) is a serious problem of public health in the Latin America and has shown an increase mortality in the Brazil. This is a systemic infectious disease involving the bone marrow, causing many hematologic manifestations. Objetives: to describe LV bone marrow features and correlate cytomorphological findings with peripheral blood parameters and the disease severity: Methodology: It is a retrospective study with gathering clinical and laboratory data of patients attended at three references hospital of Ceará State between june 2001 and August 2010. Were included 126 patients with a LV diagnosis confirmed by detection of the parasite in bone marrow and/or by positive sorology, by rK39. The slides of bone marrow aspiration of all patients were evaluated and the parasite load and the hematologic parameters were determined.The gravity was determined by the risk of death using the scoring system. Results: The age ranged from 5 months to 79 years and 74% were male. The patients from urban area accounted 68,2%. Comorbidities were associated in 31,7% patients. The more frequently finding of bone marrow were moderate/high parasite load (57,2%), dysplasia with predominance of dyserythropoiesis (80,9%), hemophagocytosis (30,1%) and granuloma (22,2%).There was one positive association between parasite load and serious neutropenia, neutrophil <500/mm3 (p=0,04), and hemophagocytosis (p=0,05). In this present study, using the model predictions based on scores was observed that 23,8% were classified as high risk of death. Most patients with a score considered with high risk of death had normocelular bone marrow, parasite load moderate/high, dyserythropoiese and dysgranulopoiese. In relation to the presence of granuloma there was a negative association statistically significant in the patients with high risk of death (p=0,02). The study points to possible diagnostic and prognostic indicators identified in the bone marrow of patients with VL.